Effect of Heat Treatment on the Anticancer Activity of Houttuynia cordata Thunb Aerial Stem Extract in Human Gastric Cancer SGC-7901 Cells. (2nd January 2021) - Liu, Jinjuan; Zhu, Xinting; Yang, Daning; Li, Rongpeng; Jiang, Jihong
Abstract: Gastric cancer is one of the most common malignant tumors in the world, and prevention through diet is one of the ways to control. Houttuynia cordata thunb.(HCT) is a plant having medicine and food function, has many biological properties. However, the effect of food style on the anticancer activity of HCT is not clear. So, we investigate the effect of heat treatment on anticancer activity of HCT. HCT extracts (heated aerial stem, heated subterraneous stem, heated leaves defined as HAS, HSS, HL, respectively, and not heated defined as NAS, NSS, NL, respectively) were obtained, and their inhibited activity were detected by alamar blue assay. The cell apoptosis was detected by DAPI staining and flow cytometry analysis. Western blot was performed to test the expression of apoptotic related protein. HCT showed the anticancer activity in four human tumor cell lines. Interestingly, heat treatment could increase the anticancer activity. In SCG-7901 cells, heat treatment increased anticancer activity of AS by 2-14 folds and induced apoptosis through regulating the intrinsic signaling pathways. Intriguingly, the caspase nine specific inhibitor blocked AS-reduced cell viability. Heat treatment increased the anticancer activity of HCT, and can be used as a dietary style for prevention of gastric cancer.